The Comparison Between English Conjunction and Indonesian Conjunctiona: A Literacy Survey - Fitri Yani (Institute of Computer Science (IOCS), 2021)
This research was carried out to describe the Conjunctions in English and Bahasa Indonesia and also suggest improving teaching grammar and speaking for which a library research was carried out to acquire the data. An available in the conclusion descriptive method was carried out to describe the findings. This research focused on the similarities and dissimilarities in the conjunctions in the two systems. The finding show that from the whole comparisson of function and position were exists this means that the application of subordinating conjunctions in speaking or writing is still in low rank.